The relationship between self-efficacy, motivation, and academic performance among students from various gender and generational groups - Mbatha, Silindele (University of the Free State, 2015)
Many students find the first year of university challenging. In South Africa, this situation is complicated further by the transformation in higher education, such as the changing profile of the student population and new access and success policies. Many factors affecting academic performance have been highlighted in research. This particular research study aimed to investigate the relationship between self-efficacy, motivation, and academic performance among students from various gender and generational groups in the South African context. A non-experimental, quantitative approach with a correlational, criterion group design was used. Non-probability, convenience sampling was used to select 271 first-year students in the Faculty of the Humanities at the University of the Free State. Data were gathered by using a research survey consisting of a biographic questionnaire and two standardised questionnaires, namely the College Self-Efficacy Instrument (CSEI) and the Motivated Strategies for Learning Questionnaire (MSLQ). Academic performance was calculated by obtaining an average of students’ marks in core modules during the first year. Statistically significant differences were found in the academic performance and academic motivation between males and females. There was no significant statistical difference with regard to the different generational groups. Academic motivation and self-efficacy explained only 0.06 % of the variance in academic performance, which is not significant. There were, however, a significant correlation between academic motivation and self-efficacy.

Baie studente vind die eerste jaar van universiteit uitdagend. In Suid-Afrika word hierdie situasie verder gekompliseer deur die transformasie in hoër onderwys, soos die veranderende profiel van die studentebevolking en nuwe toegang- en suksesbeleide. Baie faktore wat akademiese prestasie beïnvloed, is in navorsing uitgelig. Hierdie besondere navorsingstudie het ten doel gehad om die verwatskap tussen selfdoeltreffendheid, motivering en akademiese prestasie onder studente van verskeie geslag- en generasiegroepe in die Suid-Afrikaanse konteks te ondersoek. ŉ Nie-eksperimentele, kwantitatiewe benadering met ŉ korrelasionele kriteriumgroep-ontwerp is gebruik. Nie-waarskynlikheid, gerieflikheidsteekproeftrekking is gebruik om 271 eerstejaarstudente in die Fakulteit vir Geesteswetenskappe aan die Universiteit van die Vrystaat te selekteer. ŉ Navorsingopname bestaande uit ŉ biografiese vraelys en twee gestandaardiseerde vraelyste, naamlik die College Self-Efficacy Instrument (CSEI) en die Motivated Strategies for Learning Questionnaire (MSLQ), is gebruik om data te versamel. Akademiese prestasie is bereken deur ŉ gemiddelde van die studente se punte in kernmodules gedurende die eerste jaar te bekom. Statisties beduidende verskille in die akademiese prestasie en akademiese motivering tussen mans en vrouens is gevind. Daar was geen beduidende statistiese verskille ten opsigte van die verskillende generasiegroepe nie. Akademiese motivering en selfdoeltreffendheid het slegs 0.06% van die variansie in akademiese prestasie verklaar, wat nie beduidend is nie. Daar was egter ŉ beduidende korrelasie tussen akademiese motivering en selfdoeltreffendheid.
Keywords: Self-efficacy; Academic motivation; Academic performance; First-generation students; Non-first-generation students; College students; Gender identity; Dissertaton (M.A. (Psychology))--University of the Free State, 2015